PRINSIP-PRINSIP BELAJAR DAN PEMBELAJARAN DALAM PERSPEKTIF TEORI PENDIDIKAN MODERN - Sahrani, Ridwan; Muflih Naufal Irfan; Yuspiani (As-Sulthan Journal of Education, 2025)
Modern education positions the learning process as an active and reflective activity centered on the learner. Learning is no longer understood as a one-way knowledge transfer process, but rather as a dynamic interaction between learners, teachers, and the learning environment. This paper discusses the concepts of learning and teaching in modern education, the theories that underlie them, and the implications of applying modern educational principles to contemporary learning practices. The study was conducted through a literature analysis of various relevant studies in the last five years that highlight the importance of constructivism, humanism, and connectivism as the foundation for developing a modern learning system. The results of the discussion indicate that modern education demands a paradigm shift from teacher-centered learning to student-centered learning that emphasizes independence, collaboration, creativity, and lifelong learning. The application of these principles has a significant impact on improving the quality of learning, teacher competence, and active student involvement in the learning process. The implications of this research indicate that the success of modern education is highly dependent on teachers' ability to facilitate a learning environment that is adaptive to technological developments and the needs of the times.